The labour market trade-offs of pet ownership - Maris, Robbie; Cameron, Michael P. (Economics and Business Letters, 2023)
Pets are an important part of many peoples’ lives, and provide mental, physical and emotional benefits. However, the costs of pet ownership have received little attention. We investigate the association between pet ownership and wage income using data from the 2018 General Social Survey. We hypothesise that pet ownership may negatively influence income by lowering labour mobility and positively influence income by garnering valuable psychosocial attributes. We analyse interactions between pet ownership and education, pet ownership and housing tenure, and pet ownership and race to further investigate the potential labour mobility channel. Overall, we find that pet ownership decreases wage income and that these negative effects are larger for groups where mobility effects are likely higher.